Boxception: Impact Resistance Structure Using 3D Printing. Issue 8 (21st June 2019) - Sajadi, Seyed Mohammad; Owuor, Peter Samora; Vajtai, Robert; Lou, Jun; Ayyagari, Ravi Sastri; Tiwary, Chandra Sekhar; Ajayan, Pulickel M.
Abstract : The emergence of 3D printing has enabled scientists to innovate complex geometrical designs in materials which are unattainable using conventional synthesis methods. The topological material design is becoming a common occurrence aided by 3D printing. This work reports on a high load‐bearing structure by leveraging geometry using simple elastic polymers. We use the " Boxception " concept commonly used in packaging to design a structure where the open cubes are joined at their edges. The modeled structure is then printed with help of a 3D printer using polyvinyl alcohol (PVA) filament. Such design allows the outer boxes to act as shielding members to the inner‐most box. Both experimental and finite element methods (FEM) are used to understand the deformation response of the structure. Experimental investigations through compression and high impact tests along with finite element simulations conclude the inherent ability of the boxception structure to prevent failure of the inner box due to the dispersed force distribution offered by the unique structure. It is further shown that the improvement in impact and load‐bearing capacity is greatly influenced by the geometry of the structure. The unique structural design "Boxception" proposed can form primary load bearing component of sandwiched structures ensuring superior energy mitigation even under impact loads. Abstract : "Boxception" architecture consisting of interconnected boxes can results in unique mechanical behavior. The outer box deforms in such a way that it can protect inner box and hence the object kept in core. The complex design is printed using 3D printer and tested under uniaxial and impact loading. The analytical analysis provides relation between deformation behavior and geometrical parameters.